Life in its unfullness : revisiting ἀναίδειαν (Lk 11:8) in the light of papyrological evidence - Van Eck, Ernest; Van Niekerk, Robert J. (Verbum et ecclesia, 2017)
The aim of this chapter is twofold. Firstly, the chapter presents a comprehensive study of the meaning of the term άναίδειαν in extant papyrological evidence. The conclusion reached is that the term, as is the case in early Jewish and patristic writings, the LXX, Graeco-Roman literature and in early Christian writings, always carries a negative and pejorative meaning. This meaning of the term is then used to interpret the occurrence of άναίδειαν in the parable of the Friend at Midnight. Secondly, as part of a publication that celebrates the centenary of the Faculty of Theology at the University of Pretoria, a few remarks are made with regard to the Faculty of Theology’s Faculty Research Theme (Oikodome – Life in its fullness) and the attitude of άναίδειαν as depicted in the parable.